A cross-industry assessment of the flow rate-time profiles of test equipment typically used for dry-powder inhaler (DPI) testing: Part 1 – compendial apparatuses. Issue 12 (13th August 2020) - Greguletz, R.; Andersson, P. U.; Cooper, A.; Chambers, F.; Copley, M. A.; Daniels, G.; Hamilton, M.; Hammond, M.; Mohammed, H.; Roberts, D. L.; Shelton, C.; Versteeg, H. K.; et al.
Abstract: We report a cross-industry study characterizing flow rate-time profiles of equipment used for testing dry-powder inhalers (DPIs). Nine organizations used the same thermal mass flow sensor to record flow rate-time profiles at the inlet of individual participant compendial DPI test systems including either sample collection tubes (SCT), the Andersen 8-stage non-viable impactor (ACI) or the Next Generation Impactor (NGI™) with and without pre-separator (PS). The plan included some tests with a surrogate DPI consisting of one of three inlet orifices chosen to generate a 4-kPa pressure drop at each of the target final flow rates of 30, 60, and 90 l.min −1, simulating the pressure drop typical of high-, medium-, and low-resistance DPIs. When a particular surrogate DPI was present at the inlet, rise times to 90% of these target flow rates ( t 90 ) were shortest at the highest target flow rate, and decreased linearly with decreasing apparatus internal volume, following the order: NGI-PS > NGI > ACI-PS > ACI > SCT. A flow acceleration parameter was also evaluated, expressed as the slope between the rise times when the flow rate attained 20% and 80% of each final steady flow rate ( slopet 20/80 ). Flow acceleration was smallest at the lowest target flow rate, decreasing exponentially with increasing internal volume. Measurements were also made without the surrogate DPI, providing a reference condition with no resistance at the inlet to the apparatus. These flow rate-rise time profiles will be useful for those involved in evaluating equipment for characterizing DPIs and in understanding the behavior of these inhalers in development or commercial production. Copyright © 2020 American Association for Aerosol Research